1898. The Impact of Polymerase Chain Reaction Versus Antigen Based COVID-19 Testing on Subsequent Infections in Military Trainees. (15th December 2022) - Cybulski, Daniel; Matthews, Zachary; Kieffer, John; Casey, Theresa; Osuna, Angela; Kasper, Korey; Frankel, Dianne; Yun, Heather; Marcus, Joseph E
Abstract: Background: Screening large groups of individuals entering a congregate setting has been a challenge during the COVID-19 pandemic. Current Infectious Disease Society of America guidelines recommend polymerase chain reaction (PCR)-based screening in symptomatic and at-risk individuals over antigen based testing due to higher sensitivity. However, there are limited real-world data describing secondary COVID-19 cases after different arrival testing strategies. Methods: Between January 1 - August 31, 2021 all trainees attending United States Air Force Basic Military Training underwent arrival testing for COVID-19. Trainees who arrived January 1, 2021 - May 21, 2021 were tested via PCR and those from May 24, 2021 - August 31, 2021 via antigen test. All trained in groups of 30-50 and slept in communal quarters. Symptomatic secondary cases within the first two weeks of training were identified by individual as well as training group and compared based on method of arrival testing. For this study, a case cluster was defined as > 5 cases. Results: A total of 24, 601 trainees arrived during the study period with 406 (1.6%) trainees testing positive on arrival, of which 134 (33%) were symptomatic. Initial positivity rate was greater for PCR testing as compared to antigen testing (2.5% vs 0.4%, RR: 5.4, 95% CI: 4.0-7.3, p< 0.001). With PCR testing, training groups were significantly more likely to have a positive case on arrival (57% vs 11%, RR: 5.3, 95% CI: 3.7-7.7, p< 0.001). However, PCR testing was not associated with a difference in training groups with a secondary case (20% vs 22%, RR: 0.9, 95% CI: 0.66-1.2, p=0.53), number of training groups with a case cluster (4% vs 6.7%, RR: 0.61, 95% CI: 0.3-1.2, p=0.16), or number of days after arrival until development of symptomatic secondary case (median 8 vs 6.5 days, p=0.37) as compared to antigen testing. Conclusion: This study describes two strategies of arrival testing for COVID-19 in a congregate setting at high risk for disease transmission. In this study, PCR-based testing was associated with more arrival cases. However, there was no difference in the number of training groups having a secondary case or a case cluster. This study supports the utility of antigen-based arrival testing for congregate settings. Disclosures: All Authors : No reported disclosures.